Consumer data protection in Brazil, China and Germany a comparative study - Metz, Rainer; Binding, Jörg; Haifeng, Pan; Huber, Florian (Universitätsverlag Göttingen, 2016)
The rapid development of new information and communication technologies has changed people's everyday life and consumption patterns significantly. The worldwide spread of those technologies provides many innovations for consumers, but it can also bear risks, such as the indiscriminate collection, storage and cross-border flow of personal data, illegal spying on Internet activities, dissemination of personal information, and abuse of user passwords. The study deals with the current state of consumer data protection law in Brazil, China and Germany from a comparative perspective. It covers the main legal issues of consumer privacy and data protection in these countries and seeks to explain current issues and case law concerning consumer data protection from a practical perspective.